Using a drawing method to investigate pre-service teachers' beliefs, knowledge and emotions about mathematics teaching and learning. Issue 5 (20th October 2022) - Lin, Yung-Chi
ABSTRACT: This study investigated 77 Taiwanese pre-service primary teachers' beliefs, knowledge and emotions about mathematics teaching and learning by using a drawing task: specifically, creating pictures of themselves as mathematics teachers at work. Its major findings were: (1) The majority of the participants chose to illustrate a mix of teacher- and student-centred beliefs, content knowledge (CK), and positive emotions about themselves and their students. (2) Those drawings that reflected teacher-centred beliefs were more likely to contain depictions of CK and mixed emotions, whereas those that indicated student-centred beliefs were more likely to depict pedagogical content knowledge (PCK) and positive emotions. (3) Around 40% of participants who specified knowledge and emotions in their drawings seemed to feel personally more comfortable when their teaching was focused on CK. (4) Thus, in contrast to prior studies that reported mixed findings, the present research might imply that teacher educators should place greater emphasis on developing pre-service teachers' PCK than their CK, with the aim of building teachers' student-centred beliefs. (5) Lastly, we propose the term "affect-laden teacher knowledge" for the knowledge captured by the drawing task, and discuss the implications of using such knowledge in teacher education.